PENGARUH DAYA TANGGAP TERHADAPLOYALITAS PELANGGAN (Pada Nasabah Tabungan PT.BPR Sumber Pangasean Bandar Jaya) - -, Suwarto; -, Sopian (Jurnal Manajemen Magister Darmajaya, 2018)
Responsiveness is the desire of the employee as an attitude of responsiveness, responding to customers, listening to complaints, willing to help, provide prompt and accurate service, always ready to respond to customer requests with the delivery of information clear. In loyalty process, customers will be influenced by variable responsiveness. The purpose of this study is to determine the influence of responsiveness to customer loyalty at PT. BPR Sumber Pangasean Bandar Jaya. The research of analysis tool used is Spearman rank analysis to know the variable of responsiveness to customer loyalty by using computer program aids. Based on the calculation that the variable responsiveness has a correlation or relationship with customer loyalty variables. So it can be concluded that the responsiveness has a significant effect on the loyalty of the customer with a strong level of relationship. Keywords - Conscientiousness, Customer Loyalty